Social, Economic, and Spatial Transformation of the Prawirotaman Urban Kampung in Yogyakarta - Kusumaningtyas, Metta Amalia; Nurudin, Ismelia Zarfa; Wiratmoko, Dheny (Jurnal Ilmiah WUNY, 2026)
Background: Prawirotaman, a historically significant urban kampung in Yogyakarta, Indonesia, has undergone profound transformation driven by the rapid growth of tourism. Originally inhabited by descendants of Prawirotomo palace soldiers and renowned as a batik production center, the area has evolved into a vibrant tourist destination. Objectives: This study examines the social, economic, and spatial dimensions of this transformation in Prawirotaman. Method: A qualitative descriptive approach was employed through a systematic literature review of books, peer-reviewed journals, and relevant academic articles. Result: Findings reveal that tourism growth has triggered significant occupational shifts, the emergence of new social strata, and a transition from community-based social relations to commercially oriented interactions. Economically, the area has shifted from batik production to tourism services, accompanied by rising land prices, increasing investment by outside capital, and processes of commercialization and tourism-led gentrification. Spatially, the proliferation of hotels, cafes, and commercial centers has diminished public spaces and reduced pedestrian accessibility along the main corridor. Conclusion: The overall transformation of Prawirotaman reflects broader urban dynamics in Yogyakarta, pointing to the urgent need for inclusive spatial policies, local economic empowerment, and the preservation of the kampung's distinct cultural identity